Maternal inheritance of chloroplast DNA in Coffea arabica hybrids - N, Suresh; M. B, Shivanna; Ram A, Santa (Research in Biotechnology, 2012)
Intergenic spacers of chloroplast DNA (cpDNA) are very useful in phylogenetic and population genetic studies of plant species. Their integration in phylogenetic analysis leads to a deep understanding of species relationships. Mode of chloroplast DNA inheritance was investigated in the genus Coffea arabica (Rubiaceae) by polymerase chain reaction (PCR) amplification of cpDNA fragments using universal primer pair rrn23 Ã¢â‚¬â€œ trnR (ACG) region of chloroplast genome. A total of 30 F1 plants from five different C. arabica parent varieties were examined. Two crosses involving C. arabica var. Sln.10 and C. arabica var. Devamachy, and C. arabica var.S.881 and another cross involving C. arabica var. Agaro with C. arabica var. Tafarikela were analyzed. Length polymorphism was observed in all three hybrids at rrn23 Ã¢â‚¬â€œ trnR (ACG) region of cpDNA. In each case, it was the maternal cpDNA marker that appeared in the F1 individuals. Further it was observed that the length polymorphismÃ‚Â observed within parental plants led to the identification of five different banding patterns at rrn23 Ã¢â‚¬â€œ trnR (ACG) region of coffee cpDNA. The possible reasons for the observed differences are discussed.